Ketika Stress Beraksi Islam Punya Solusi - Zaenal Abidin (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2009)
Stress is a mental condition that may results in the destruction of personal life, both physically and mentally. Stress may be driven by internal and external factors. Since it can negatively affect an individual, Islam offers some solution to face such condition